Nécropole familiale et mémoire funéraire d’un praticien à Marquion (Pas-de-Calais) - Claire Barbet; Muriel Pardon-Labonnelie; Clémence Chalvidal; Marlène Aubin (Gallia)
At the end of the 1st c. AD, seven privileged burials, two of which are in mausoleums, were excavated in a private area located 150 m southwest of a villa in Atrebato-Nervian territory. The monumental aspect of the vaults of these graves, the selection and abundance of artefact deposits and the distinctiveness of some of the objects provide remarkable evidence of activities linked to cosmetic and therapeutic care.